The impact of subjective norms, behavioral control and attitude factors on the purchase Intention of OTOP snacks food products : a case study among international consumers in Phuket-Thailand - Mahamat Abdourrahmane (Prince of Songkla University, 2015)
Thesis (M.B.A., (Business Administration))--Prince of Songkla University, 2014